Inhibitory and teratogenic effects of xylene on the early developmental stages of the sea urchin tripneustes gratilla - Enolpe, Liaia B. (2016)
Abstract: Xylene is an aromatic hydrocarbon and when it is released into the marine environment, it is detected in the upper depths of the seawater column. The embryos of sea urchin are vulnerable to toxicants because they are planktonic. Sea urchin embryos were exposed to different xylene concentrations (180, 360, 540, 720 and 900 μg∙L-1). Responses were reported as inhibitions on fertilization, early cleavage, mid cleavage, late cleavage and blastulation with the endpoints at 0.5, 2, 3, 4 and 5 h, respectively. Inhibitions increased significantly across different developmental stages. Inhibitions on fertilization was significantly different at varying times of exposure. Abnormalities were counted and rated degree. Degree of abnormality of fertilized eggs was concentration-dependent. For cleaving cells and blastula, degree of abnormality was dependent on the time of exposure. EC50 values for xylene were estimated using a probit analysis: 737 μg∙L-1 on fertilization, 868 μg∙L-1 on early cleavage, 764 μg∙L-1 on mid cleavage, 594 μg∙L-1 on late cleavage and 618 μg∙L-1 on blastulation. The study provided data on the dose-dependent inhibitory effects of xylene. It also provided evidence on the dependence on the percent abnormality on fertilization on the varying times of exposure as well as the degrees of abnormality of the specific embryonic stages.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu